Tinjauan Hukum Terhadap Kasus Tertangkapnya 55 Orang Asing yang Berada di Idonesia Pelaku Penipuan Menggunakan Media Elektronik: Sebuah Studi Kriminologi Menggunakan Perspektif Opportunity Theory - Hutabarat, Habel Refo; Ashari, Hasan; Hernanda, Reyhan (Peneliti.net, 2024)
The phenomenon of globalization accompanied by the development of information and communication technology has brought various positive and negative impacts on world society. Relations between communities are becoming easier, in fact the pattern of these relations has changed from local and regional to global and even blurring regional boundaries. Apart from positive impacts such as increasing relationships, this relationship pattern has apparently brought many new modes of crime, for example fraud. The existing opportunities mean that fraud, which was previously carried out directly and conventionally, now involves the use of information and communication technology and is carried out beyond national borders. This challenges countries in the world to formulate regulations or laws governing public relations in the cyber world (cyber space law). For example, a case occurred in Indonesia in early 2023, where there was an arrest of a group of fraudsters who had committed fraud against foreigners outside Indonesian territory using electronic media, carried out by 55 Chinese citizens from Indonesia. In this article the author tries to examine how the follow-up of this case is in accordance with existing regulations compared to the real decisions taken by the Indonesian government. The government's decision to deport the perpetrators turned out to be the best decision in line with what the author discusses in this article.